Lactate threshold as a measure of aerobic metabolism in resistance exercise - Dominguez, R.; Mate-Munoz, J. L.; Serra-Paya, N.; Garnacho-Castano, M. (International Journal of Sports Medicine, 2018)
In resistance training, load intensity is usually calculated as the percentage of a maximum repetition (1RM) or maximum number of possible repetitions (% of 1RM). Some studies have proposed a lactate threshold (LT) intensity as an optimal approach for concurrent training of cardiorespiratory endurance and muscle strength, as well as an alternative in resistance training. The objective of the present study was to analyze the results obtained in research evaluating the use of LT in resistance training. A keyword and search tree strategy identified 14 relevant articles in the Dialnet, Elsevier, Medline, Pubmed, Scopus and Web of Science databases. Based on the studies analyzed, the conclusion was that the LT in resistance exercises can be determined either by mathematical methods or by visual inspection of graphical plots. Another possibility is to measure the intensity at which LT might coincide with the first ventilatory threshold (VT1). Since performing an exercise session at one`s LT intensity has been shown to accelerate the cardiorespiratory response and induce neuromuscular fatigue, this intensity could be used to set the training load in a resistance training program.